ANALISIS KESALAHAN PENULISAN HURUF KAPITAL OLEH MAHASISWA PGSD SEMESTER II KELAS 3 UNIKA SANTO THOMAS SUMATERA UTARA - Liana Siburian (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to analyze the errors of capital letter writing by PGSD students in second semester of class 3 of school year 2017/2018. This research uses qualitative descriptive method with research subject ayaitu PGSD student of Semester II Class 3 is qualitative descriptive method. The application of the method in this research takes the following steps: inventory data through questionnaire, data description, and data classification. The results of the study note that every student needs to write because writing is part of student life. In order to have no problem in writing the capital letters, it is necessary to improve the writing of capital letters in the first sentence, the first letter of direct passage, the first letter of honorary title, ancestry, and religion followed by the name of the person, the first letter of the name of the nation, the tribe and the language.Keywords: Error Analysis Capital Writing